2003
DOI: 10.1001/archneur.60.7.949
|View full text |Cite
|
Sign up to set email alerts
|

Cinguloparietal Atrophy Distinguishes Alzheimer Disease From Semantic Dementia

Abstract: Alzheimer disease is associated with a specific pattern of cortical atrophy compared with SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
64
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 41 publications
11
64
0
Order By: Relevance
“…The findings of our MRI study highlight, as expected, significant GM reduction in the left temporal neocortex (temporal pole, and inferior, middle and superior temporal gyri), and at a lesser degree, in the right temporal neocortex, in accordance with previous quantitative volumetric [7,22,39] and VBM [4,25,26,29,49] studies. This pattern of results is in agreement with the severe semantic memory deficits in our group of SD patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of our MRI study highlight, as expected, significant GM reduction in the left temporal neocortex (temporal pole, and inferior, middle and superior temporal gyri), and at a lesser degree, in the right temporal neocortex, in accordance with previous quantitative volumetric [7,22,39] and VBM [4,25,26,29,49] studies. This pattern of results is in agreement with the severe semantic memory deficits in our group of SD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Left amygdala atrophy in SD has recently been shown in VBM [4,25] and in volumetric [39,78] MRI studies, and seems to be more pronounced than in Alzheimer"s disease. Davies et al [12] have also stressed the involvement of the parahippocampal gyrus, more precisely, the perirhinal and entorhinal cortices, in SD.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…10 In addition, voxel-based morphometry (VBM), 11 as an automated unbiased analysis of the differences in tissue concentration throughout the brain on structural MR imaging scans, has been widely used in brain tissue loss studies in AD. [12][13][14][15][16] These VBM studies reported bilateral gray matter loss in the hippocampus. However, the above 2 methods cannot accurately detect regional abnormalities of the hippocampal atrophy.…”
mentioning
confidence: 97%